2018
DOI: 10.3390/genes9090454
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Imbalances in Argentinean Patients with Congenital Conotruncal Heart Defects

Abstract: Congenital conotruncal heart defects (CCHD) are a subset of serious congenital heart defects (CHD) of the cardiac outflow tracts or great arteries. Its frequency is estimated in 1/1000 live births, accounting for approximately 10–30% of all CHD cases. Chromosomal abnormalities and copy number variants (CNVs) contribute to the disease risk in patients with syndromic and/or non-syndromic forms. Although largely studied in several populations, their frequencies are barely reported for Latin American countries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
(82 reference statements)
2
8
0
Order By: Relevance
“…We found 22q11 imbalances in 23% of the patients analyzed by MLPA with conotruncal CHD, similar to our previous results [ 28 ]. Although the 22q11 imbalances were most prevalent among patients presenting MCA, 22% of the patients with isolated conotruncal CHD had a 22q11 microdeletion or duplication, similar to other reports [ 15 , 16 , 17 , 89 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found 22q11 imbalances in 23% of the patients analyzed by MLPA with conotruncal CHD, similar to our previous results [ 28 ]. Although the 22q11 imbalances were most prevalent among patients presenting MCA, 22% of the patients with isolated conotruncal CHD had a 22q11 microdeletion or duplication, similar to other reports [ 15 , 16 , 17 , 89 ].…”
Section: Discussionsupporting
confidence: 92%
“…MLPA analysis was performed using the SALSA P250-B1 MLPA kit (MRC-Holland, Amsterdam, The Netherlands) as previously described [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cohort study found that rs2832616 and rs1943950 SNPs and CNV in RIPK4 and ZBTB21 genes within chromosome 21 in a Down syndrome patient, suggesting multiple gene aberrations [175]. 22q11 deletion, 17p13.3, 4q35, and TBX1 deletions are highly associated with conotruncal defect abnormalities [176] and 3.76 Mb de novo gain of 9q34.2-q34.3 is associated with tetralogy of Fallot with the absence of pulmonary valve [177]. In addition, serious cardiac malformations have been documented due to duplication and deletion in GATA4 and SOX7 genes respectively [178] as well as in NODAL gene [179].…”
Section: Chromosomal Abnormalities Copy Number Variants and Chdsmentioning
confidence: 99%
“…Congenital heart defects comprise some of the most common, serious, and clinically important groups/types of birth defects [ 1 , 2 , 3 ]. These defects consist of a heterogenous group of structural heart malformations (i.e., conotruncal heart defects that affect the cardiac outflow tract) that are thought to have at least some shared genetic basis [ 4 , 5 , 6 , 7 ]. Some conotruncal heart defects involve a deviation from the normal position of the origin of the aorta and pulmonary trunk, in which case the great vessels are said to be transposed.…”
Section: Introductionmentioning
confidence: 99%